Optimization of vancomycin dosing regimens to achieve therapeutic targets in critically Ill patients in Thailand - Thitinat Dedkaew (2018)
It is essential to rapidly achieve therapeutic vancomycin concentrations in critically ill patients with gram-positive bacterial infections. This study aimed to determine optimal vancomycin dosing regimens for critically ill patients. Using an external dataset - therapeutic drug monitoring concentration data from 51 critically ill patients receiving vancomycin, we validated a population pharmacokinetic model to describe vancomycin plasma concentrations over time. The final population pharmacokinetic model was used to simulate different vancomycin doses for patients with varying degrees of renal function in order to determine the percentage of patients achieving therapeutic targets. Based on simulations, less than 90% of patients achieved a vancomycin trough concentration (Ctrough) ≥ 15 mg/L following administration of the standard vancomycin maintenance doses of 1000 mg every 12 hr (for patients with a creatinine clearance (CrCL) ≥ 50 mL/min) or 1000 mg every 24 hr (for those with CrCL 30-50 mL/min). Model predictions showed that to ensure ≥ 90% of patients achieve a target vancomycin Ctrough, 1250 mg every 6 hr (for CrCL ≥ 50 mL/min) and 1000 mg every 8 hr (for CrCL 30-50 mL/min) are needed. In conclusion, alternative vancomycin dosing regimens may improve the percentage of attaining target vancomycin Ctrough at steady state in critically ill patients in Thailand. However, routine monitoring of vancomycin Ctrough and serum creatinine are also recommended to ensure therapeutic and toxicity outcomes.